Acceptability of childhood screening: a systematic narrative review. (April 2021) - Carlton, J.; Griffiths, H.J.; Horwood, A.M.; Mazzone, P.P.; Walker, R.; Simonsz, H.J.
Abstract: Objectives: A systematic narrative literature review was undertaken to assess the acceptability of childhood screening interventions to identify factors to consider when planning or modifying childhood screening programs to maximize participation and uptake. Study design: This is a systematic narrative literature review. Methods: Electronic databases were searched (MEDLINE, EMBASE, PsycINFO via Ovid, CINAHL, and Cochrane Library) to identify primary research studies that assessed screening acceptability. Studies were categorized using an existing theoretical framework of acceptability consisting of seven constructs: affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy. A protocol was developed and registered with PROSPERO (registration no. CRD42018099763) Results: The search identified 4529 studies, and 46 studies met the inclusion criteria. Most studies involved neonatal screening. Programs identified included newborn blood spot screening (n = 22), neonatal hearing screening (n = 13), Duchenne muscular dystrophy screening (n = 4), cystic fibrosis screening (n = 3), screening for congenital heart defects (n = 2), and others (n = 2). Most studies assessed more than one construct of acceptability. The most common constructs identified were affective attitude (how a parent feels about the program) and intervention coherence (parental understanding of the program, and/or the potential consequences of a confirmed diagnosis). Conclusions: The main acceptability component identified related to parental knowledge and understanding of the screening process, the testing procedure(s), and consent. The emotional impact of childhood screening mostly explored maternal anxiety. Further studies are needed to examine the acceptability of childhood screening across the wider family unit. When planning new (or refining existing) childhood screening programs, it is important to assess acceptability before implementation. This should include assessment of important issues such as information needs, timing of information, and when and where the screening should occur.